2016
DOI: 10.1159/000449008
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Hippocampal Stimulation for Failed Unilateral Anterior Temporal Lobectomy in Patients with Bilateral Temporal Lobe Epilepsy

Abstract: Aims: To prospectively study the surgical outcomes of unilateral anterior temporal lobectomy (ATL) in patients with intractable bilateral temporal lobe epilepsy (TLE) as well as two-staged contralateral hippocampal stimulation in patients after failed unilateral ATL. Methods: Eighteen carefully selected patients with bilateral TLE underwent unilateral ATL. Five cases with failed ATL underwent two-staged contralateral hippocampal stimulation. Seizure control and changes in intelligence quotient (IQ), memory quo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Limitations of this study include the inclusion of only 1 randomized control trial, 7 5 blinded studies, 13,29,37,42,44 and 8 prospective trials, 9,13,19,26,29,37,[40][41][42]44 with the remaining 12 studies being retrospective case reports and case series. Furthermore, it is difficult to analyze and compare the effectiveness of DBS between studies, as different metrics and outcomes are reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations of this study include the inclusion of only 1 randomized control trial, 7 5 blinded studies, 13,29,37,42,44 and 8 prospective trials, 9,13,19,26,29,37,[40][41][42]44 with the remaining 12 studies being retrospective case reports and case series. Furthermore, it is difficult to analyze and compare the effectiveness of DBS between studies, as different metrics and outcomes are reported.…”
Section: Discussionmentioning
confidence: 99%
“…24 Five patients had previous surgery in an attempt to treat their epilepsy. 2,5,9,20,37 The operations included a biopsy to identify a possible epileptogenic lesion, 2 a right precentral frontal lobe resection 5 and a left anterior temporal lobectomy 9 to attempt seizure reduction, and VNS; 37 1 patient had already undergone right fontal lobectomy, complete corpus callosotomy, VNS, left temporal lobectomy, and posterior quandrantectomy. 20 These procedures did not achieve the desired seizure reduction, and DBS was offered as an alternative treatment.…”
Section: Seizure Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Velasco et al [11] have demonstrated seizure frequency improvement in 9 children with Lennox-Gastaut after the insertion of bilateral CM electrodes. DBS has also been considered in children who have already undergone resective surgery without significant post-operative seizure reduction [14,24,25]. DBS has been used in four children who had a history of status epilepticus with an improvement in seizure frequency in three of these children [15,26].…”
Section: Predictors Of Responsementioning
confidence: 99%
“…Approximately 40% of patients experience continuous postoperative seizures after resective surgery (5,6). The percentage of postoperative seizure freedom is only 10% in patients who have undergone alleviation surgery or neuromodulation due to a nonlocalizable epileptogenic zone or an epileptogenic zone involving the eloquent area (7)(8)(9)(10). Therefore, it is necessary to explore novel treatments for drug-resistant epilepsy.…”
Section: Introductionmentioning
confidence: 99%